A comparative study on the determinants of consumer’s behavioural intention to adopt ehailing application: Malaysia vs Singapore - Cheong, Jia Ern; Lee, Jing Heng (2019)
This research investigated the determinants that affect the behavioural intention of hailing users in Malaysia and Singapore. UTAUT model was adopted. The independent variables were performance expectancy, effort expectancy, facilitating conditions, social influences and also perceived risk; and the dependent variable was behavioural intention to adopt ehailing application. Primary data were collected through online questionnaires, Google Form. The target respondents were ehailing users in Malaysia and Singapore. The questionnaires were sen t out to the target respondents through social media platform, referrals, and also natural contacts. This research used a convenience sampling technique. 203 responses were collected from Malaysia and 104 were collected from Singapore. The collected data w as processed by using the Statistical Package for the Social Sciences (SPSS) programme. The results were then compared with the previous similar studies done by other researchers. xiii